2005
DOI: 10.1002/ajmg.a.30775
|View full text |Cite
|
Sign up to set email alerts
|

The new Wolf–Hirschhorn syndrome critical region (WHSCR‐2): A description of a second case

Abstract: The Wolf-Hirschhorn syndrome (WHS), is a well known contiguous gene syndrome characterized by microcephaly, hypertelorism, prominent glabella, epicanthal folds, cleft lip or palate, cardiac defects, growth and mental retardation and seizures. The currently accepted WHS critical region (WHSCR) is localized between the loci D4S166 and D4S3327, where a deletion seems to generate all the clinical manifestations of the syndrome. Here we present a patient with a subtelomeric deletion of 4p16.3 showing growth and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
(32 reference statements)
2
37
0
2
Order By: Relevance
“…In addition, they considered additional key features likely due to haploinsufficiency of other genes in the region, representing true contiguous gene syndrome phenotypes. Support to the existence of the WHSCR2 was presented by Rodriguez et al [2005]. Thus, WHS appears as a distinct disorder characterized by a recognizable facial gestalt and clinical manifestations in which the phenotype is highly related to both the size and the location of deletions.…”
Section: To the Editormentioning
confidence: 85%
“…In addition, they considered additional key features likely due to haploinsufficiency of other genes in the region, representing true contiguous gene syndrome phenotypes. Support to the existence of the WHSCR2 was presented by Rodriguez et al [2005]. Thus, WHS appears as a distinct disorder characterized by a recognizable facial gestalt and clinical manifestations in which the phenotype is highly related to both the size and the location of deletions.…”
Section: To the Editormentioning
confidence: 85%
“…Red-red-green means presence of inversion (c). Fifty to hundred nuclei were analysed in individual subject patients except two (MG and patient 97), as previously reported (Zollino et al 2003;Rodriguez et al 2005).…”
Section: Characterization Of the 4p Deletion By Molecular Cytogeneticsmentioning
confidence: 99%
“…Genotype-phenotype correlation studies have shown a relationship between deletion size and severity of clinical presentation. [6][7][8] Of patients meeting the minimal diagnostic criteria, 9 the smallest terminal deletion identified was B1.9 Mb, 1, 9,10 suggesting that genes within this interval of 4p16.3 are responsible for the core features of WHS. 8,11 Beyond this region, the loss of additional critical genes appears to be responsible for variably present features, such as congenital malformations or hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…The more proximal critical region (WHSCR) was delineated first 15 and mapping within this 165-kb interval identified two genes, WHSC1 and WHSC2. 16,17 The identification of two WHS patients with more distal 4p16.3 terminal deletion breakpoints 9,10 shifted and expanded the critical region (WHSCR-2) to a 300-600-kb region overlapping the 5 0 end of WHSC1 and encompassing LETM1, a candidate gene for seizures. 18 Although there is evidence to support a contribution of WHSC1 and LETM1 to the core WHS phenotype, 19,20 focal deletions or mutations of these genes have not been identified in WHS patients.…”
Section: Introductionmentioning
confidence: 99%